2015
DOI: 10.1038/srep16476
|View full text |Cite
|
Sign up to set email alerts
|

Attenuation of Histone Methyltransferase KRYPTONITE-mediated transcriptional gene silencing by Geminivirus

Abstract: Although histone H3K9 methylation has been intensively studied in animals and a model plant Arabidopsis thaliana, little is known about the evolution of the histone methyltransferase and its roles in plant biotic stress response. Here we identified a Nicotiana benthamiana homolog of H3K9 histone methyltransferase KRYPTONITE (NbKYP) and demonstrated its fundamental roles on methylation of plant and virus, beside of leading to the suppression of endogenous gene expression and virus replication. NbKYP and another… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 49 publications
(95 reference statements)
0
22
0
2
Order By: Relevance
“…In the presence of Hpa Hiks1, the fine regulation of RPP7 transcripts mediated by both IBM2 and FPA favors accumulation of a long transcript to induce a rapid and specific immune response . Similarly, the importance of H3K9 methylation in resistance to viruses has been described (Sun et al, 2015), and the virulence of geminiviruses requires a viral protein that inhibits expression of the main plant H3K9 methyltransferase, KYP. To reinforce the action of KYP, rapid modulation of IBM1 gene expression, mediated by both FPA and IBM2, is likely essential.…”
Section: Resultsmentioning
confidence: 92%
“…In the presence of Hpa Hiks1, the fine regulation of RPP7 transcripts mediated by both IBM2 and FPA favors accumulation of a long transcript to induce a rapid and specific immune response . Similarly, the importance of H3K9 methylation in resistance to viruses has been described (Sun et al, 2015), and the virulence of geminiviruses requires a viral protein that inhibits expression of the main plant H3K9 methyltransferase, KYP. To reinforce the action of KYP, rapid modulation of IBM1 gene expression, mediated by both FPA and IBM2, is likely essential.…”
Section: Resultsmentioning
confidence: 92%
“…Virus encoded suppressors of gene silencing (VSR) have been implicated in virus pathogenicity (Csorba et al, 2015, Derrien et al, 2012, Garcia-Ruiz et al, 2015). Although the suppressors encoded by CMGs have not been well characterized, it is suggested that ACMV-CM AC4 targets post-transcriptional gene silencing (PTGS) whereas EACMV and ICMV AC2 potentially target both PTGS and transcriptional gene silencing (TGS) (Sun et al, 2015, Vanitharani et al, 2004). ICMV isolate ICMV-SG was recently shown to accumulate higher virus titer and greatly represses TGS in N .…”
Section: Discussionmentioning
confidence: 99%
“…ICMV isolate ICMV-SG was recently shown to accumulate higher virus titer and greatly represses TGS in N . benthamiana compared to a less virulent isolate ICMV-Dha (Sun et al, 2015). Targeting PTGS and TGS by EACMV KE2 (K201) AC2 may contribute to the high pathogenicity of the former as compared to ACMV-CM reported here.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This result correlates with our observed reduction of sRNAs in centromeric and pericentromeric regions (rich in H3K9me2) and the observed changes in CHH and CHG methylation (tightly associated with H3K9me2). Interestingly KYP has been previously associated with the regulation of the defense against geminiviruses (Castillo-Gonzalez, Liu et al, 2015, Raja, Sanville et al, 2008, Sun, Tee et al, 2015 and the maintenance of baminobutyric acid (BABA)-induced priming of the salicylic acid (SA)-dependent defense response (Luna, Lopez et al, 2014). In summary, our proof-of-concept analysis indicates that, indeed, mutants in different layers of epigenetic regulation show enhance resistance against aphid settlement.…”
Section: Epigenetic Mutants Show Enhanced Defense Against Aphidsmentioning
confidence: 99%